Ethanol Fraction of Corn Silk (Zea mays L.) to Decrease Uric Acid Levels in Male White Mice - Laila Susanti (Fakultas MIPA Universitas Tulang Bawang Lampung, 2019)
Corn silk (Zea mayz L.) were empirically used by the community in some regions as traditional remedies for hypertension,kidney stones,diabetes mellitus, urinary tractinfections and gout. This study aimed to determine the effect of corn silk ethanol fraction on decrease uric acid levels in male white mice.corn silk were extracted by macerate used 70% ethanol for 4 days.Urin acid test was performed on male mice induced by beef liver for 7 days.25 mice were grouped into 5 groups, groups dose I, II and III weregiven a fraction at a dose of 27.5 mg / bwBB, 55 mg / bwBB and 110 mg / bwBB, control given Na.CMC 0.5% and as positive controls were given allopurinol dose of 13 mg / bwBB. The five groups were treated orally 1 time a day for 7 days. Decreased uric acid levels were measured and observed on days 7 using an acid (easy touch). The results of ANOVA statistical analysis showed that negative controls gave a significant difference with positive controls, dose I, II and III because the sig value was